Parallel operation of diode‐rectifier based HVDC link and HVAC link for offshore wind power transmission. Issue 18 (28th May 2019) - Yu, Lujie; Li, Rui; Xu, Lie
Abstract : This paper investigates the integration of large offshore wind farms using parallel HVAC and diode‐rectifier based HVDC (DR‐HVDC) systems. Three different operation modes, i.e. HVAC operation mode, DR‐HVDC operation mode and parallel operation mode are investigated. A wind turbine control scheme including distributed control and centralised control is proposed to ensure the stable operation of the offshore wind farms under different operation modes. The proposed control requires no switching of the distributed control strategy when the operation mode is changed. Moreover, power flow between the DR‐HVDC link and HVAC link under parallel operation can be well controlled with the centralised control. Simulation results in PSCAD/EMTDC verify the proposed control during transition among the three operation modes.